Oral health-related quality of life in patients with dental anxiety - Mehrstedt M, John MT, To¨nnies S, Micheelis W. (Blackwell Synergy, 2007)
To investigate the frequency of impaired oral healthrelated quality of life (OHRQoL) in patients with dental anxiety